(untitled) (Faridpur Medical College Journal, 2020)
Antenatal care (ANC) is very important for all women for their own health and their neonates. This study was done to observe the impact of antenatal care on perinatal asphyxia. This case-control study was conducted at Neonatology Department of Dhaka Medical College Hospital, Dhaka from July 2014 to December 2014. Fifty neonates with perinatal asphyxia (Group I) and fifty neonates without perinatal asphyxia (Group II) were selected as study subjects. After selection, informed written consent was taken. Then data were collected by face to face interview of the mother. The mean age of neonates was 49.0±72.1 hours in group I and 55.8±63.9 hours in group II. Majority (80.0%) of the neonates had birth weight 2.5- 4.0 kg in group I and only 22(44.0%) neonates had birth weight 2.5-4.0 kg in group II. Almost half (48.7%) of the mothers received antenatal check-up at UHC/FWC/MCWC in group I and 20(41.7%) in group II. It was observed that 19(38.0%) mothers received antenatal care from untrained Dai in group I and 42(84.0%) in group II. Only 30.0% of the mothers received adequate antenatal check-up in group I and 68.0% in group II. Mothers having baby with perinatal asphyxia received significantly less number of ANC. Faridpur Med. Coll. J. Jan 2019;14(1): 34-36